Peculiarities of Application of Innovative Check Methods in Professional Teacher-Philologistsʼ Preparation - Svitlana Dubrova (Pedagogical Discourse, 2015)
The author of the article attempted to identify the peculiarities of application of innovative check methods in professional teacher-philologistsʼ preparation. It was found out that for checking the level of students’ subject knowledge and professional skills are used innovative check methods along with traditional in the educational process of high school. These are the methods of test and programed checks. It was considered the classification of types of tests according to the training purpose, the methodology and specifications of its making, the advantages and disadvantages of the test check method. Tests are clarified according to the training purpose: 1) knowledge test (facts, concepts, laws, theories). The reproduction of knowledge; 2) abilities test (performing of certain actions which are based on the gain knowledge); 3) abilities test (critical analyzing of the trained material without assistance); 4) abilities test (creative application of the gain knowledge during solving non-standard tasks). The methodology of its making is: 1) definition of the test purpose; 2) selection and structuring of the teaching material; 3) selection the most appropriate form of the tests; 4) definition of the criterion of estimation. Tests may include: short (10-20 tasks); medium (300 tasks); long (more than 300 tasks). The peculiarity of the test check method is its uniformity and standardization; the possibility to check all students simultaneous; the possibility to check the whole material array, not selective; the possibility to make systematically assessments of achievements.The test check is realized by modern computer programs in institutions of higher education. Its gives an opportunity to receive the    test result immediately, without direct and personal contact between teacher and students. Also, we considered the features, advantages and disadvantages of programmed test check.